Appreciating beauty in Islam - Spahic, Omer (ISTAC, 2011)
This paper aims to discuss the notion of beauty from a perspective of the Islamic worldview. The paper shows that beauty in Islam and the utter formation of Islamic aesthetics - just like any other segment of Islamic culture and civilization - cannot be disengaged from the body of Islamic teachings and values and be treated in isolation. From conceptualizing beauty, over creating and appreciating beautiful objects and experiences, and finally to valuing and elevating the idea of beauty to such a level as to relate the same to the Ultimate Transcendental Reality, i.e. God, who is the source of all beauty, Islam provides an inspiration and guidance so that an actual and unambiguous aesthetic realization is duly accomplished on earth. The paper is divided into the following sections: 1) The beauty of Allah’s creation, 2) Defining beauty from different perspectives, 3) Islam on the duality of existence, 4) The believer’s universal outlook on life shapes his perception of beauty, 5) Recognizing beauty through a sixth sense, 6) Islam’s keenness for expressing and enjoying beauty, 7) Two erroneous views on beauty in Islam, 8) Conclusion: the beauty of Allâh.